A inteligência artificial como instrumento de democratização e suas contribuições para a gestão da água: uma análise entre Brasil e Espanha - Pagnussat, Renan Carlos (2024)
This dissertation addresses relevant aspects of Artificial Intelligence, which, due to its magnitude, has become an integral part and essential component of today's society, which has been marked by countless and constant social and digital transformations and paradigm shifts. Some say that Artificial Intelligence emerges as a disruptive technology, as it breaks with certain practices and standards that had been adopted until then. However, from another perspective, there is an understanding that Artificial Intelligence emerges as an inclusive tool, therefore, it is not restricted to certain sectors or social aspects, being used in countless areas and professions within society. For this reason, this research is guided by the objective of verifying how this tool can, in a certain way, given its essentiality today, contribute to the development of public policies and, consequently, to the rational use of water, a finite natural resource that is essential to life on earth, both in Brazil and in Spain, due to the double degree of the master's degree obtained at the University Institute of Waters in Alicante, Spain. To this end, some specific objectives were established, namely: understand Artificial Intelligence, its concept, legality, objectives, risks and responsibilities; analyze the promotion for the development of public policies aimed at the rational use of water, verifying the main legislations, the challenges faced and the measures that could be adopted for the conscious reuse of water in Brazil and Spain; and examine how Artificial Intelligence could contribute to the development of public policies and the rational use of water in Brazil and Spain. The methodology used in this work is based on the operational logic of the inductive method based on the chosen theme and the bibliographic research technique supported by institutional instruments and documents, constitutional charters, infra-constitutional legislation, books, publications in periodicals and conference proceedings. The research line of this dissertation is included in Constitutional and Democratic Jurisdiction, in the area of ​​concentration New Paradigms of Law, of the Stricto Sensu Postgraduate Program - Master's in Law of the School of Legal Sciences of the University of Passo Fundo.